Market and society the great transformation today - Hann, Chris 1953-; Hart, Keith 1943- (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership